1149 Treat The Pda? Comparison of the Outcome in Treated and Restrictive Treated VLBW Infants. (October 2012) - Linnemann, K; Kriegsmann, C; Stenger, R; Fusch, C; Heckmann, M
Abstract : Background: Management of PDA is discussed controversial. In 2008 we changed our regime from restrictive treatment of PDA to treatment of PDA. Aim: Comparing the outcome of VLBW-Infants with two therapeutic PDA regimes: A restrictive treated and B treated PDA. Method: Historical cohort- study of VLBW infants born between 2005 and 2007 (group A: n=120; treatment of PDA only if weight gain was inadequate (< 10g/kg/d in spite of optimized nutrition) and between 2008 and 2010 (group B: n=126; treatment of "hemodynamic significant" PDA, diagnosed on the basis of reverse diastolic flow in the Truncus coeliacus or renal arteries < day 3). Other NICU guidelines were not changed but probiotics for NEC-prophylaxis started in 2011. Outcome measures: rate of NEC, BPD, IVH, neurological outcome (Laewen questionnaire). Results: In group A the rate of ductus closure was significantly lower than in group B (A: 19/53, B: 29/45; p<0.01). PDA rate in both groups did not differ significantly (A: 53/120; B: 45/126; p=0.67). Surgical closure rate was 9% in both groups. The incidences of NEC, BPD and IVH were not different between groups. The results of the neurological outcome were not significantly different, but follow up reached only 60% so far. Conclusions: Changes in practice of PDA treatment in VLBW infants resulted in a 28% increase in frequency of medical or surgical closure of PDA without change in short or long term neonatal outcome. Further controlled randomized studies are needed to confirm our results on restrictive treatment of PDA.